Use of paracetamol for suicide and non-fatal poisoning in the UK and France: are restrictions on availability justified?. Issue 2 (April 1997) - Gunnell, D; Hawton, K; Murray, V; Garnier, R; Bismuth, C; Fagg, J; Simkin, S
Abstract : OBJECTIVE: To investigate the relationship between the availability of paracetamol and its use for overdose and suicide. DESIGN: Analysis of routinely collected information on time trends for paracetamol suicides, non-fatal overdoses, and sales. SETTING: England and Wales and France. RESULTS: There were strong correlations between trends in paracetamol sales in the UK and trends in non-fatal paracetamol overdose in Oxford between 1976 and 1993 (Spearman's r = 0.86; 95% confidence interval (CI) 0.54, 0.96) and between paracetamol sales and non-fatal overdoses in France between 1974 and 1990 (r = 0.99; 95% CI 0.97, 1.00). Sales figures were also correlated with paracetamol related suicides in both England and Wales, 1983-91 (r = 0.72; 95% CI 0.11, 0.94) and France, 1974-90 (r = 0.79; 95% CI 0.50, 0.92). Similarly strong relationships were observed between trends in non-fatal overdoses and suicide by paracetamol poisoning in England and Wales (r = 0.85; 95% CI 0.61, 0.95) and France (r = 0.79; 95% CI 0.50, 0.92). It is estimated that approximately 32, 000 overdoses involving paracetamol occur annually in England and Wales. Fatality rates from paracetamol overdose were four times as high in England and Wales (0.4%, 95% CI 0.38, 0.46) as in France (0.1%, 95% CI 0.06, 0.17). CONCLUSION: Trends towards greater availability of paracetamol are paralleled by increases in its use for both non-fatal overdose and suicide. Paracetamol related morbidity and mortality seem to be less frequent in France where the quantity of paracetamol in a single purchase is limited. Although not conclusive, these data add to a body of evidence which suggests that restrictions in the quantity of paracetamol available as a single purchase in the UK may reduce suicide and liver failure related to paracetamol.